Research('s) Sweet Hearts: Experimental Biomedical Models of Diabetic Cardiomyopathy - Richter, Claudia; Hinkel, Rabea (Frontiers in Cardiovascular Medicine, 2021)
Diabetes and the often accompanying cardiovascular diseases including cardiomyopathy represent a complex disease, that is reluctant to reveal the molecular mechanisms and underlying cellular responses. Current research projects on diabetic cardiomyopathy are predominantly based on animal models, in which there are not only obvious advantages, such as genetics that can be traced over generations and the directly measurable influence of dietary types, but also not despisable disadvantages. Thus, many studies are built up on transgenic rodent models, which are partly comparable to symptoms in humans due to their genetic alterations, but on the other hand are also under discussion regarding their clinical relevance in the translation of biomedical therapeutic approaches. Furthermore, a focus on transgenic rodent models ignores spontaneously occurring diabetes in larger mammals (such as dogs or pigs), which represent with their anatomical similarity to humans regarding their cardiovascular situation appealing models for testing translational approaches. With this in mind, we aim to shed light on the currently most popular animal models for diabetic cardiomyopathy and, by weighing the advantages and disadvantages, provide decision support for future animal experimental work in the field, hence advancing the biomedical translation of promising approaches into clinical application.